HISTORICAL GENESIS AND MODERN CLASSIFICATION OF RADICALISM AS A SOCIAL PHENOMENON (Western European Journal of Historical Events and Social Science, 2026)
This article examines the historical genesis and modern classification of radicalism as a social phenomenon. Radicalism is analyzed as a complex socio-political process that has evolved throughout different historical stages of human development. The study explores the early manifestations of radicalism in ancient social protest movements, its development during the Middle Ages in the form of religious movements, and its transformation during the political and industrial changes of the eighteenth and nineteenth centuries. Special attention is given to the emergence of radical ideologies in the twentieth century and the appearance of new forms of radicalism in the context of globalization and technological development. The article also discusses various modern classifications of radicalism, including political, religious, ethnic, and social radicalism, as well as ideological and practical forms. Furthermore, the process of radicalization and its influence on contemporary society, particularly among youth, is analyzed. The study concludes that understanding the historical development and typology of radicalism is essential for developing effective strategies to prevent radicalization and ensure social stability and security